Cybersemiotics: A New Foundation for Transdisciplinary Theory of Information, Cognition, Meaning, Communication and Consciousness - Brier, Søren (Signs - International Journal of Semiotics, 2011)
We need to realize that a paradigm based on the view of the universe that makes irreversible time and evolution fundamental, forces us to view man as a product of evolution and therefore an observer from inside the universe. This changes the way we conceptualize the problem and role of consciousness in nature compared to what Descartes did with his dualistic paradigm. The theory of evolution forces us theoretically to conceive the natural and social sciences as well as the humanities together in one framework of unrestricted or absolute naturalism, where consciousness is part of nature. This has influenced the exact sciences to produce theories of information and self-organization in order to explain the origin of life and sense experiences, encouraged biological thinking to go into psychology and social science in the form of theories of selfish genes, socio-biology and evolutionary psychology. But these approaches have still not satisfactorily led to an understanding of why and how certain systems have the ability to produce sense experiences, awareness and meaningful communication. The theories of the phenomenological life world and the hermeneutics of communication and understanding seem to defy classical scientific explanations. The humanities therefore send another insight the opposite way down the evolutionary ladder, with questions like: What is the role of consciousness, signs and meaning in evolution? These are matters that the exact sciences are not constructed to answer in their present state. Phenomenology and hermeneutics point out to the sciences that they have prerequisite conditions in embodied living conscious being imbued with meaningful language and a culture. One can see the world view that emerges from the work of the sciences as a reconstruction back into time of our present ecological and evolutionary self-understanding as semiotic intersubjective conscious cultural historical creatures, but unable to handle the aspects of meaning and conscious awareness. How can we integrate these two directions of explanatory efforts? The problem is that the scientific one is without concepts of qualia and meaning, and the phenomenological-hermeneutic “sciences of meaning” do not have a foundation of material evolution. A modern interpretation of C.S. Peirce’s pragmaticistic evolutionary and phaneroscopic semiosis in the form of a biosemiotics is used and integrated with N. Luhmann’s evolutionary autopoietic system theory of social communication. This framework, which integrates cybernetics and semiotics, is called Cybersemiotics.